Ligand-based substituent-anchoring design of selective receptor-interacting protein kinase 1 necroptosis inhibitors for ulcerative colitis therapy - Jing Zhu; Meng Xin; Congcong Xu; Yuan He; Wannian Zhang; Zhibin Wang; Chunlin Zhuang (Elsevier, 2021)
Receptor-interacting protein (RIP) kinase 1 is involved in immune-mediated inflammatory diseases including ulcerative colitis (UC) by regulating necroptosis and inflammation. Our group previously identified TAK-632 (5) as an effective necroptosis inhibitor by dual-targeting RIP1 and RIP3. In this study, using ligand-based substituent-anchoring design strategy, we focused on the benzothiazole ring to obtain a series of TAK-632 analogues showing significantly improving on the anti-necroptosis activity and RIP1 selectivity over RIP3. Among them, a conformational constrained fluorine-substituted derivative (25) exhibited 333-fold selectivity for RIP1 (Kd = 15 nmol/L) than RIP3 (Kd > 5000 nmol/L). This compound showed highly potent activity against cell necroptosis (EC50 = 8 nmol/L) and systemic inflammatory response syndrome (SIRS) induced by TNF-α in vivo. Especially, it was able to exhibit remarkable anti-inflammatory treatment efficacy in a DSS-induced mouse model of UC. Taken together, the highly potent, selective, orally active anti-necroptosis inhibitor represents promising candidate for clinical treatment of UC.